2020
DOI: 10.1136/jitc-2019-000337
|View full text |Cite|
|
Sign up to set email alerts
|

Consensus guidelines for the definition, detection and interpretation of immunogenic cell death

Abstract: Cells succumbing to stress via regulated cell death (RCD) can initiate an adaptive immune response associated with immunological memory, provided they display sufficient antigenicity and adjuvanticity. Moreover, multiple intracellular and microenvironmental features determine the propensity of RCD to drive adaptive immunity. Here, we provide an updated operational definition of immunogenic cell death (ICD), discuss the key factors that dictate the ability of dying cells to drive an adaptive immune response, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
686
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 757 publications
(757 citation statements)
references
References 332 publications
7
686
0
Order By: Relevance
“…Both surface and soluble molecules are required to induce ICD in response to chemotherapeutic drugs such as anthracyclines, oxaliplatin, taxanes, alkylating agents, and proteasome inhibitors [2][3][4]. The exposure of calreticulin (CRT) on cell surface and the release of ATP and High Mobility Group Box 1 (HMGB1) protein are potent signals that engage dendritic cells (DCs), stimulate phagocytosis and antigen processing, and expand cytotoxic CD8 + T-lymphocytes (CTLs) with antitumor activity [2,5]. CRT, a chaperon protein usually residing within endoplasmic reticulum (ER), translocates to the plasmamembrane, bound to the ERp57 protein.…”
Section: Introductionmentioning
confidence: 99%
“…Both surface and soluble molecules are required to induce ICD in response to chemotherapeutic drugs such as anthracyclines, oxaliplatin, taxanes, alkylating agents, and proteasome inhibitors [2][3][4]. The exposure of calreticulin (CRT) on cell surface and the release of ATP and High Mobility Group Box 1 (HMGB1) protein are potent signals that engage dendritic cells (DCs), stimulate phagocytosis and antigen processing, and expand cytotoxic CD8 + T-lymphocytes (CTLs) with antitumor activity [2,5]. CRT, a chaperon protein usually residing within endoplasmic reticulum (ER), translocates to the plasmamembrane, bound to the ERp57 protein.…”
Section: Introductionmentioning
confidence: 99%
“…ICD includes immunogenic apoptosis, necrosis/necroptosis, pyroptosis, and autophagic cell death. Endoplasmic reticulum (ER) stress response, PAMPs, and DAMPs play important roles in OV-induced ICD [70].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Recent studies demonstrated that genetically modified OVs, armed with a therapeutic gene, mediated clinical responses. FDA approved T-VEC was safe and, in advanced melanoma, resulted in a 10.8% complete response rate, significantly higher than systemic GM-CSF alone [70]. Other examples are poxvirus (Pexavec, TRICOM, TroVax) [74,75], and adenovirus (ONCOS-102) [76].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently described phenomenon, termed immunogenic cell death (ICD) (5,6), is a form of cell death that induces an immune response from the host. ICD is distinguished from classical apoptosis and other non-immunogenic or tolerogenic forms of cell death by several hallmarks, including release of ATP and HMGB1 and surface exposure of calreticulin (5)(6)(7). In cancer patients, ICD-based anti-tumor immune responses are linked to beneficial outcomes produced by some conventional chemotherapeutic agents (8)(9)(10)(11).…”
mentioning
confidence: 99%